2017
DOI: 10.18535/jmscr/v5i12.87
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality in a Tertiary Care Hospital of Central India: A 5 years Review

Abstract: The key to the progress of a country lies in reducing it's maternal morbidity and mortality. The maternal mortality rate has gone down since 1980 however it has still not achieved the target level hence to give a better assessment to the problem of maternal mortality, a retrospective study on maternal mortality ratio and it's causes has been carried out. Objective of the study was to find out the maternal mortality ratio and its causes of five years (2012)(2013)(2014)(2015)(2016)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
4
2
0
Order By: Relevance
“…Severe anaemia contributed only 6.6%. These findings were similar with that of many other similar studies [19,20,23,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Severe anaemia contributed only 6.6%. These findings were similar with that of many other similar studies [19,20,23,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 93%
“…High maternal mortality ratio of 632 per lakh live births in a tertiary care hospital of Central India was observed by Lilare R.R. during 2016 [19]. Similar study conducted by Nair A during 2016 in tertiary care hospital in Maharashtra also revealed very high MMR of 410/ 1 lakh live births which is similar to the present study [20].…”
Section: Discussionsupporting
confidence: 88%
“…Main direct obstetric causes were hemorrhage, hypertensive disorders of pregnancy and sepsis. Similar findings were reported by other studies [8][9][10][11][12][13]. In the period during COVID pandemic, there was change in causes of maternal mortality.…”
Section: Discussionsupporting
confidence: 90%
“…About 75.69% mothers were multiparous and 75.13% were not registered for antenatal checkup. Similar demographic profile of study population was reported by other studies [8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 87%
“…Out of all indirect causes of maternal mortality, infectious diseases contribute to maximum percentage. 10 Out of 14 patients, 7 patients had full term normal vaginal deliveries, 7 patients underwent emergency caesarean deliveries and one had early pregnancy failure (Figure 4). 4 out of 7 patients had caesarean under subarachnoid block and 3 patients received general anaesthesia due to low platelet count.…”
Section: Discussionmentioning
confidence: 99%